2021
DOI: 10.1111/mpp.13030
|View full text |Cite
|
Sign up to set email alerts
|

Identification of RipAZ1 as an avirulence determinant of Ralstonia solanacearum in Solanum americanum

Abstract: Ralstonia solanacearum causes bacterial wilt disease in many plant species. Type III‐secreted effectors (T3Es) play crucial roles in bacterial pathogenesis. However, some T3Es are recognized by corresponding disease resistance proteins and activate plant immunity. In this study, we identified the R. solanacearum T3E protein RipAZ1 (Ralstonia injected protein AZ1) as an avirulence determinant in the black nightshade species Solanum americanum. Based on the S. americanum accession‐specific avirulence phenotype o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 88 publications
1
11
0
Order By: Relevance
“…The loss of this protein possibly avoids recognition by the host defense system and makes P781 virulent to mandevilla. RipAZ1 was identified as an avirulence determinant in Solanum Americanum (Moon et al, 2021) strengthening our hypothesis. For osteospermum RipS1 was identified as a putative virulence factor that is not present in P824.…”
Section: Discussionsupporting
confidence: 80%
“…The loss of this protein possibly avoids recognition by the host defense system and makes P781 virulent to mandevilla. RipAZ1 was identified as an avirulence determinant in Solanum Americanum (Moon et al, 2021) strengthening our hypothesis. For osteospermum RipS1 was identified as a putative virulence factor that is not present in P824.…”
Section: Discussionsupporting
confidence: 80%
“…Some T3Es with important functions are selected out largely depending on the comparative analysis of the effectors. For instance, the recently reported R. solanacearum avirulence effectors RipJ and RipAZ1 are identified by the comparative genomic analysis of two strains with different virulence against S. pimpinellifolium and S. americanum , respectively ( Moon et al, 2021 ; Pandey and Moon, 2021 ). Similarly, by comparing all the effectors of PeaFJ1 and HA4-1, we found that most of the effectors are exactly identical with the counterparts of R. solanacearum HA4-1.…”
Section: Resultsmentioning
confidence: 99%
“…The research revealed that IPO1609 carries a 77 kb genomic deletion, which is responsible for almost complete loss of pathogenicity of the strain ( Gonzalez et al, 2011 ). Recently, the R. solanacearum avirulence effectors RipJ and RipAZ1 were identified by the comparative genomic analysis of two strains with different virulence against Solanum pimpinellifolium and S. Americanum , respectively ( Moon et al, 2021 ; Pandey and Moon, 2021 ). In the current study, we performed a comprehensive comparative analysis of the genome sequences of R. solanacearum strain PeaFJ1 and other strains, especially HA4-1.…”
Section: Introductionmentioning
confidence: 99%
“…Some are regarded as weeds but others are consumed as food and medicine in various countries 43 . Importantly, these species carry valuable natural sources of genetic resistance to diseases such as potato late blight and bacterial wilt 25,29,33 . Variation for resistance to other pests and diseases is being investigated but when defining corresponding genes, reference genomes are highly advantageous.…”
Section: Discussionmentioning
confidence: 99%
“…S. americanum is a globally distributed Solanaceae species, which is resistant to many pathogens including Phytophthora infestans and Ralstonia solanacearum 25,29,33 . Four S. americanum accessions SP1102, SP2271, SP2273 and SP2275 were selected for sequencing based on their variation in resistance to late blight (Supplementary Fig.…”
Section: Genome Assembly and Gene Model Prediction Of Solanum Americanummentioning
confidence: 99%